Surveillance Strategies for Sarcoma: Results of a Survey of Members of the Musculoskeletal Tumor Society. (13th July 2016) - Greenberg, David D.; Crawford, Brooke
Abstract : Background . Surveillance is crucial to oncology, yet there is scant evidence to guide strategies. Purpose . This survey identified sarcoma surveillance strategies for Musculoskeletal Tumor Society (MSTS) members and rationales behind them. Understanding current practice should facilitate studies to generate evidence-based surveillance protocols. Methods . Permission was granted by the Research and Executive Committee of the MSTS to survey members on surveillance strategies. First, the questionnaire requested demographic and clinical practice information. Second, the survey focused on clinicians' specific surveillance soft tissue and bone sarcoma protocols. Results . 20 percent of MSTS members completed the survey. The primary rationale for protocols was training continuation, followed by published guidelines, and finally personal interpretation of the literature. 95% of the respondents believe that additional studies regarding appropriate surveillance protocols are needed. 87% reported patient concerns regarding radiation exposure from surveillance imaging. For soft tissue and bone sarcoma local recurrence, responders identified surgical margin, histologic grade, and tumor size as the most important factors. For metastases, important risk factors identified included histologic grade, tumor size, and histologic type. Protocols demonstrated wide variation. Conclusion . This survey demonstrates that surveillance strategies utilized by MSTS members are not evidence-based, providing rationale for multi-institutional studies. It also confirms the public health issue of excessive radiation exposure.